Inclusive Strategy Model for Strengthening Entrepreneurship among Muslims with Disabilities: A Penta-Helix and Co-Creation Approach - Anik Puji Handayani; Budi Sutiono Pratama Nugraha; Hisham Al Ghunaimi; Gigih Aulia Hilmiawan; Melvin Rahma Sayuga Subroto (Global Review of Islamic Economics and Business, 2026)
Muslims with disabilities face multidimensional barriers that limit their participation in formal employment, making entrepreneurship a strategic avenue for economic independence and social inclusion. This study develops a conceptual model of resilience for Muslim entrepreneurs with disabilities by integrating internal and external support factors through a Penta-Helix and co-creation perspective. Employing a qualitative approach that combines an extensive literature review with semi-structured interviews involving practitioners, policymakers, academics, and disability-focused NGOs, the study identifies key factors shaping entrepreneurial resilience. The findings reveal that resilience is not an innate trait but an emergent capability cultivated through the interaction of internal psychological strengths such as self-efficacy, persistence, opportunity recognition, innovativeness, and risk-taking and structured external support systems. Islamic values further reinforce emotional stability, moral discipline, and purpose-driven motivation. Despite these strengths, structural challenges persist, including limited market access, inadequate financial literacy, insufficient mentoring, and enduring social stigma. To address these barriers, the proposed model presents inclusive ecosystem solutions, including Sharia-compliant financing, integrated incubators, collaborative co-working hubs, mentoring platforms, and advocacy programs involving government, industry, academia, communities, and the media. This model contributes to the literature on disability entrepreneurship by offering a holistic, value-integrated, and ecosystem-oriented framework.